Raw data for paper: Modulation of the molecular arrangement in artificial and biological membranes by phospholipid-shelled microbubbles - Stride, E (University of Oxford, 2016)
Measurements of generalised potential and membrane viscosity from quantitative microscopy examinations of vesicles and cells.